2006
DOI: 10.1002/cne.21224
|View full text |Cite
|
Sign up to set email alerts
|

Functional and anatomical connection between the paraventricular nucleus of the thalamus and dopamine fibers of the nucleus accumbens

Abstract: The shell of the nucleus accumbens (NacSh) receives a dense innervation from dopamine (DA) neurons in the ventral tegmental area (VTA) and from glutamate neurons in the paraventricular nucleus of the thalamus (PVT). The present study examined in urethane-anesthetized rats the effects of electrical stimulation of the PVT on DA levels in the NacSh as measured with amperometry and chronoamperometry. Stimulation of the PVT (40 Hz, 1.0 ms, 400 microA, 5 seconds) resulted in a brief increase in electrochemical curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 104 publications
(126 reference statements)
5
98
0
1
Order By: Relevance
“…Although no distinct clusters emerged in prelimbic cortex and nucleus accumbens core (Figure 1d and e), we found distinct clusters for the infralimbic region that are partially explained by the alcohol consumption history of the rats (Figure 1f). Strikingly, low-and highconsuming animals almost completely segregated based on their metabolome profiles in the nucleus accumbens shell (Figure 1g) that aligns well with the known role of this region in alcohol reward (Imperato and Di Chiara, 1986;Di Chiara and Imperato, 1988;Pontieri et al, 1995;Howland et al, 2002;Parsons et al, 2007). Our results therefore indicate that excessive alcohol consumption indeed affects neurometabolism in a brain region-specific manner, particularly in the infralimbic-accumbens shell circuit.…”
Section: Resultssupporting
confidence: 80%
“…Although no distinct clusters emerged in prelimbic cortex and nucleus accumbens core (Figure 1d and e), we found distinct clusters for the infralimbic region that are partially explained by the alcohol consumption history of the rats (Figure 1f). Strikingly, low-and highconsuming animals almost completely segregated based on their metabolome profiles in the nucleus accumbens shell (Figure 1g) that aligns well with the known role of this region in alcohol reward (Imperato and Di Chiara, 1986;Di Chiara and Imperato, 1988;Pontieri et al, 1995;Howland et al, 2002;Parsons et al, 2007). Our results therefore indicate that excessive alcohol consumption indeed affects neurometabolism in a brain region-specific manner, particularly in the infralimbic-accumbens shell circuit.…”
Section: Resultssupporting
confidence: 80%
“…Regarding PV, they reported that of the midline nuclei of thalamus, PV was the predominant source of afferents to the shell of ACC, and while also pronounced to the core, were shared by other midline thalamic groups to the core . Several subsequent studies have confirmed 'massive' PV projections to ACC, and further showed that a fairly significant percentage of PV fibers to ACC collateralize to other sites (Meredith and Wouterlood, 1990;Su and Bentivoglio, 1990;Brog et al, 1993;Freedman and Cassell, 1994;Moga et al, 1995;Bubser and Deutch, 1998;Otake and Nakamura, 1998;Erro et al, 2002;Pinto et al, 2003;Parsons et al, , 2007, mainly to the mPFC (Bubser and Deutch, 1998;Otake and Nakamura, 1998) and to the amygdala (Su and Bentivoglio, 1990).…”
Section: Pv Projections: Comparisons With Previous Studiesmentioning
confidence: 85%
“…If cocaine-induced generation of silent synapses and the subsequent unsilencing of these synapses are indeed a synaptogensis process, this leads to a quantitative increase in the number of synapses, thus strengthening PVT to NAc transmission. The PVT is often regarded as an 'interface' that receives arousal-provoking stimuli signals, including visceral, reward, circadian, and sensory signals, and sends output signals to the NAc that regulate sensorimotor responses and motivated behaviors (Kelley et al, 2005;Parsons et al, 2007;Colavito et al, 2015). An overall strengthening of the PVT-to-NAc projection may thus increase and bias the responsiveness of the NAc to corresponding internal and external stimuli, contributing to the sensitized state of the animal after drug withdrawal.…”
Section: Circuitry Consequencesmentioning
confidence: 99%